Influence of bio-psycho-social factors on physical activity in Spanish undergraduate education students - Sanz-Martín, Daniel; Ubago-Jiménez, José Luis; Cachón-Zagalaz, Javier; González-Valero, Gabriel (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
It is essential to know the precise levels of compliance with physical activity recommendations for each population group and the determinants that condition them directly and indirectly. A cross-sectional study was designed for Spanish undergraduate education students with the following aims: 1) To analyse the influence of body mass index, Mediterranean diet, social network addiction, emotional intelligence and sitting time as predictors of compliance with physical activity recommendations; 2) To design an explanatory model to establish the relationships between body mass index, Mediterranean diet, addiction to social networks, emotional intelligence and sitting time of students who comply with physical activity recommendations. The binary logistic regression model designed had good fit (X2=4.15, p=0.04; R2 = 0.126; Hosmer-Leneshow p> 0.05). The structural equation model designed had good fit (CFI= 0.970, NFI=0.906, IFI= 0.971, TLI = 0.960, and RMSEA0.039). It can be concluded that the regression model predicts 12.6% of compliance with physical activity recommendations. Likewise, in the regression and structural equation models, time spent in moderate-vigorous physical activity is positively related to body mass index and adherence to the Mediterranean diet.